A framework for evaluating and ranking ontologies. (1st January 2013) - Bouiadjra, Abderrazak Bachir; Benslimane, Sidi Mohamed
Reusing the increasing number of available ontologies is extremely important for the advancement and the growth of Semantic Web, because it reduces the required costs, efforts and amount of time to build new ontologies. However, the lack of standard frameworks to assess their quality and their suitability for being used in a specific context remains a barrier to their wide adoption and reuse. To address this problem, we present in this paper a framework for evaluating and ranking ontologies, with three distinctive features. First, it provides an advanced retrieval mechanism that gathers the best set of candidate ontologies. Second, it defines a rich set of metrics for assessing several ontology aspects. Third, it supplies a helpful way for visualising and interpreting the results. We implemented and evaluated the proposed metrics. The results of these evaluations are presented, indicating the usefulness of the overall framework.